Application of 3D-DIC to characterize the effect of aggregate size and volume on non-uniform shrinkage strain distribution in concrete. (February 2018) - Chen, Yang; Wei, Jiangxiong; Huang, Haoliang; Jin, Wen; Yu, Qijun
Abstract: To elucidate the effect of aggregate size and volume on the non-uniform strain distribution in concrete, drying shrinkage of mortar and concretes were determined with 3D digital image correlation (3D-DIC). The distribution of shrinkage displacements and strains in mortar and concrete were analyzed. The results show that 3D-DIC makes it possible to measure non-uniform displacement distributions initiated by shrinkage in mortar and concrete. The non-uniformity became more remarkable with drying time. The presence of aggregates larger than 5 mm in concrete have locally changed the displacement and strain fields. Aggregates within 5–25 mm make non-uniform strain of concrete more fluctuant, especially when the aggregate size is larger than 10 mm. The maximum and minimum principal strain distributions became more heterogeneous with decreasing volume of aggregates.